The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3892/etm.2020.9319
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quality of life and disease severity of pediatric patients with atopic dermatitis

Abstract: Atopic dermatitis (AD) is a complex, chronic skin disorder with a broad spectrum of clinical aspects, characterized by abnormal skin barrier function. This has a significant impact on patients' quality of life (QoL), which represents a crucial parameter for their wellbeing. This study assessed the QoL of patients with AD by following parameters such as itching, disturbance of sleep, disturbance of play activity, and community activities. The study included 64 patients clinically diagnosed with AD, aged 0 to 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(18 reference statements)
1
7
0
1
Order By: Relevance
“…Hence, AD had a significant impact on their QoL. Similar results were also reported in Romania 2 and Denmark. 3 Furthermore, the impairment of parents’ QoL was highly correlated to the severity of AD in infants aged <5 years.…”
supporting
confidence: 84%
“…Hence, AD had a significant impact on their QoL. Similar results were also reported in Romania 2 and Denmark. 3 Furthermore, the impairment of parents’ QoL was highly correlated to the severity of AD in infants aged <5 years.…”
supporting
confidence: 84%
“…Some studies in Colombia, Argentina, and Brazil evaluated the impact of AD on QoL, according to multiple scales (Skindex, Dermatology Life Quality Index, Infants' Dermatitis Quality of Life Index, Dermatitis Family Impact Questionnaire) 67–70 . In line with the global findings, 63 these studies unanimously agree that QoL and disease activity are correlated.…”
Section: Unmet Needs Of Ad In Lamentioning
confidence: 84%
“…A previous study similarly identified emotional distress and sleep disturbance as the most reported QoL subdomains (after itching/scratching) in pediatric patients with AD aged 0–16 years [ 32 ]. Other studies have reported the highest impact of AD to be on school/holidays, itch, and free time/hobbies (for patients aged 5–9 years) or school/holidays, friendships, and either itch or free time/hobbies (for patients aged 10–16 years) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%